Gender disparities in academic dermatology in Japan: Results from the first national survey. Issue 1 (April 2021) - Kishibe, Mari; Saijo, Yasuaki; Igawa, Satomi; Maruyama, Ayano; Tamagawa-Mineoka, Risa; Nishida, Emi; Higashi, Yuko; Komine, Mayumi; Tada, Yayoi; Aoyama, Yumi; Hide, Michihiro; Ishida-Yamamoto, Akemi
Highlights: A wide gender gap exists in the academic society of dermatology. We studied faculty members' academic productivity for the first time in Japan. Women lecturers and asst. professors had room for improvement in academic productivity. Abstract: Background: A wide gender gap exists in many fields in Japan, including the academic society of dermatology. Women are substantially underrepresented in the highest academic ranks. Objective: We aimed to clarify the possible factors contributing to the current gender gap in the field of academic dermatology and to recommend necessary measures to decrease the gender gap. Methods: We performed a cross-sectional study of faculty members' academic productivity at the dermatology departments of all the educational institutions in Japan in 2019. Results: Women had significantly lower academic productivity than men. A significant gender difference in academic productivity was found in lecturers and assistant professors but not in associate professor and professor positions. This gender difference was still significant after normalizing the productivity for career length. Conclusion: Our findings suggest the need to encourage women lecturers and assistant professors to improve their academic achievement to decrease the gender gap in academic dermatology.